How risky is caring for emergency patients at risk of malpractice litigation: a population based epidemiological study of Taiwan's experiences - Tsai Shin-Han; Yang Che-Ming; Chiu Wen-Ta (BMC, 2009)
Abstract Background Emergency medicine has generally been considered a high risk specialty. The purpose of this study is to assess the risk of being sued in the district courts for caring emergency room (ER) patients from the perspective of epidemiology. Methods This research was designed to be a retrospective population based cohort study. We intended to find out the incidence of litigations arising from ER patients and that of birth inpatients in Taiwan, and computed their relative risks. The inclusion criterion was set to be incidents transpired in the time period of 1998 to 2002. The study materials included the reimbursement claim dataset of the National Health Insurance from 1998 to 2002, and the district court decision database of the Judicial Yuan from 1999 to 2006. Results The average annual incidence rate of becoming a plaintiff for ER patients is 0.86 per million, and for birth patients is 33.5 per million. There is a statistically significant difference between birth patients and ER patients. The relative risk comparing ER patients against birth inpatients is 0.03. Conclusion The findings of this population based study indicate that the patient population emergency physicians are facing in Taiwan have relatively lower risks of developing litigation in comparison with the patients that come to give birth. Due to the large volume of ER patients, malpractice still pose a major threat in the emergency department, and misdiagnosis remains the major complaint of plaintiffs in subsequent litigations.